Respuesta :

1. (4x+5y)(2x-3y)+3xy= 4x*2x-4x*3y+5y*2x-5y*3y+3xy=8x^2-12xy+10xy-15y^2+3xy= 8x^2+xy-15y^2

2. (2x^2+3)(4x+5)-8x(x^2-2)=2x^2*4x+2x^2*5+3*4x+3*5-8x*x^2+8x*2=

=8x^3+10x^2+12x+15-8x^3+16x=

=10x^2+28x+15

Answer:

1. [tex]8x^2+xy-15y^2[/tex]           2. [tex]10x^2 + 28x + 15[/tex]

Step-by-step explanation:

For Question 1:

[tex](4x + 5y) (2x - 3y) + 3xy[/tex]

= [tex]8x^2 - 12xy + 10xy - 15y^2 + 3xy[/tex]

[tex]=8x^2+xy-15y^2[/tex]       (cannot simplify any further)

For Question 2:

[tex](2x^2 + 3)(4x +5) - 8x(x^2 -2)[/tex]

[tex]=8x^3 + 10x^2 + 12x + 15 - 8x^3 + 16x[/tex]

[tex]=10x^2 + 28x + 15[/tex]         (cannot simplify any further)

ACCESS MORE